Profile analysis of newborns with perinatal anoxia in the Neonatal Intensive Care Unit of a private maternity hospital in Sergipe (Research, Society and Development, 2023)
Aim: To evaluate the profile of newborns with gestational age ≥ 35 weeks with perinatal anoxia in the Neonatal Intensive Care Unit (NICU) of a private maternity hospital in Aracaju, Sergipe. Methodology: This is a descriptive, cross-sectional and observational clinical study. A convenience sample was used, consisting of all newborns with a gestational age ≥ 35 weeks, admitted to the NICU from January 1, 2019 to December 31, 2020. Neonates outside the gestational age of the study or incomplete medical records were excluded. An Apgar score less than 7 at the 5th minute was used to define neonatal anoxia (NA). The analysis used Pearson's Chi-Square, Fisher's exact, Shapiro-Wilk, Mann-Whitney and Kruskal-Wallis tests, in addition to descriptive data. A significance level of 5% was applied. Results: The final sample consisted of 127 children, mostly male (63.7%), with normal birth weight (75.2%) and adequate weight for gestational age (79.6%). The mean weight and mean gestational age were 2,982.7 grams (± 649.5) and 37.5 weeks (± 1.6), respectively. The groups with and without NA did not show significant epidemiological differences. A higher risk of anoxia was found in those born vaginally (p=0.001) and in those with acute perinatal events (p=0.003). Small size for gestational age was a risk factor for death. Conclusion: Acute perinatal events and vaginal birth are risk factors for NA. Newborns who are small for gestational age have worse outcomes. Future studies detailing the types of birth to analyze the association with NA may be useful.